PERGESERAN RITUAL SOSIAL DALAM TRADISI OMED-OMEDAN - Ari Putra Sahadewa, I Gusti Made; Nugroho, Wahyu Budi; Krisna Aditya, I Gst. Ngr. Agung (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
Omed-omedan is a unique tradition in Bali, this tradition is located in Banjar Kaja, Sesetan Village, Denpasar. However, in its implementation, this tradition has often received sharp criticism from the public and the national media, this is due to the inclusion of inappropriate actions to be presented to the public. The purpose of this research is to re-understand the Omed-omedan tradition which has experienced shifts in both meaning and ritual in it, and to understand the social dimensions of this tradition. This research uses a qualitative approach with descriptive and explanative types. The theory used in this research is the constructionism theory of Clifford Geertz, Omed-omedan today has finally taken steps to improve their image, with the festival that accommodates this tradition, in line with Their Balinese Ajeg movement seeks to preserve this tradition so that meaning can be conveyed correctly. Keywords: Omed-omedan, Sesetan, shifting social rituals